International Legal Backgrounds to Regulate Counteractions Against of Foreign Terrorist Fighters and Interstate Law - A. G. Volevodz (Московский журнал международного права, 2017)
Combating foreign terrorist fighters (individuals who travel abroad to participate in acts of violence as part of an uprising or of a non-State armed group) is a relatively recent challenge to the global counterterrorism effort. In addition to their direct participating in terrorist activities in the territories of foreign States, their returning is a serious destabilizer for many States. Upon return and after having received training for terrorism in Syria and Iraq, these individuals may either join local groups or set up sells of the international terrorist networks. They actively contribute to the commission of terroristic acts, collection of funds to finance their terroristic activities, spreading of violent extremism and recruiting new members. Practically, an active international cooperation is a prerequisite to a successful combating of foreign terrorist fighters. This cooperation involves developing coordinated preventative measures in respect of travelling abroad for the purpose of terrorism as well as punishing those responsible for participating in terroristic activities in a State, which is not that of their residence. This article examines the international legal basis for combating foreign terrorist fighters. It includes the UN Security Council resolution 2178 (2014) on threats to international peace and security caused by foreign terrorist fighters and the Riga Additional Protocol to the Council of Europe Convention on the Prevention of Terrorism of 22 October 2015, opened for signature. The article further shows how the need to combat foreign terrorist fighters has led to the criminalization of their activities in many States. It concludes that the Russian legislator should also criminalize the fact of travelling abroad for the purpose of terrorism and other actions of the foreign terrorist fighters and their accomplices.